The Influence of Location on Purchasing Decisions at Indomaret Pasar Minggu in Tapung, Kampar Regency, Riau - Yusnidar, Yusnidar; Agusta, Muhammad Adrian; Rahmat, Adi (Luxury: Landscape of Business Administration, 2024)
The purpose of this study was to determine the effect of location on purchasing decisions at Indomaret Pasar Minggu, Tapung District, Kampar Regency, Riau. The sample in this study was 96 consumers. The data analysis used was validity test, reliability test, normality test, heteroscedasticity test, simple linear regression, determination coefficient test and hypothesis test (t-test). Based on the results of the study, it is known that the overall location variable determination coefficient has an influence of 44.9% on purchasing decisions, while the remaining 55.1% is influenced by other factors not studied by the author. The results of the hypothesis test show t count (8.746)> t table (1.985) with sig 0.000 <sig 0.05, so it can be concluded that there is a significant influence on Location on Purchasing Decisions at Indomaret Pasar Minggu, Tapung, Tapung Regency, Kampar Riau.